2011
DOI: 10.1007/s00380-011-0130-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of a model for prediction of coronary atherosclerotic regression: evaluation of high-density lipoprotein cholesterol level and peripheral blood monocyte count

Abstract: Monocytes and high-density lipoprotein cholesterol (HDL-C) play important roles in the process of coronary atherosclerosis. We hypothesized that a reasonable predictive model of coronary plaque regression might be constructed using the change in the peripheral monocyte count and the serum HDL-C level. The plaque volume, as assessed by volumetric intravascular ultrasound, was measured at the baseline and after 6 months of pravastatin therapy in 114 patients with coronary artery disease. After 6 months of pravas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 29 publications
1
26
0
1
Order By: Relevance
“…Cetin and colleagues reported in their study which recruited 2661 patients a significant positive correlation between MHR and Gensini score 22 . In this study which included 4980 patients, we also found that MHR was positively associated with Gensini score, indicating that MHR could be an independent indicator to predict the prevalence and severity of CAD, which was consistent with previous studies 19,20,22 . In addition, this study presents a number of important strengths.…”
Section: Discussionsupporting
confidence: 92%
“…Cetin and colleagues reported in their study which recruited 2661 patients a significant positive correlation between MHR and Gensini score 22 . In this study which included 4980 patients, we also found that MHR was positively associated with Gensini score, indicating that MHR could be an independent indicator to predict the prevalence and severity of CAD, which was consistent with previous studies 19,20,22 . In addition, this study presents a number of important strengths.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, in a Study to Evaluate the Effect of Rosuvastatin on Intravascular Ultrasound-Derived Coronary Atheroma Burden (ASTEROID), rosuvastatin at a dose of 40 mg/d for 24 months regressed coronary atherosclerosis by intravascular ultrasound and quantitative coronary angiography [230]. In a similar fashion, elevation in HDL-C was significantly related to atherosclerotic plaque regression in patients with coronary artery disease after six months of pravastatin therapy, as revealed by multiple regression analysis [231]. The beneficial effect of this statin on coronary atherosclerosis was correlated with both a reduction in LDL-C and an increment in HDL-C [230].…”
Section: Clinical Trialsmentioning
confidence: 89%
“…In humans, a direct correlation between the high‐cholesterol levels and increased counts of peripheral mononuclear phagocytes was also found therefore reflecting the stimulating contribution of lipids on the levels of monocytes and neutrophils in the circulation . Treatment with lipid‐lowering agents caused decrease in levels of both neutrophils and monocytes thereby suggesting for the positive link between hypercholesterolaemia and pro‐atherogenic monocytosis/neutrophilia.…”
Section: Introductionmentioning
confidence: 87%